Selestial mechanics in the works of Kiril Popoff (in Bulgarian) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2008)
We trace the role of selestial mechanics in the research of the prominent Bulgarian mathematician and physisist Kiril Popov.